2011
DOI: 10.1111/j.1744-9987.2011.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet Hydrochloride Therapy for Secondary Hyperparathyroidism in Hemodialysis Patients

Abstract: This study compared the efficacy of a cinacalcet-based regimen with unrestricted conventional therapy (vitamin D and phosphate binders) for achieving Kidney Disease Outcome Quality Initiative (K/DOQI) targets for dialysis patients. In this multicenter, prospective study, hemodialysis patients with poorly controlled secondary hyperparathyroidism (SHPT) were randomized to receive a cinacalcet-based regimen (n=55) or a conventional therapy (n=27). Doses of cinacalcet, vitamin D sterols, and phosphate binders were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…Although the use of calcitriol, active vitamin D analogs, and cinacalcet has been shown to reduce PTH and although cinacalcet reduced rates of parathyroidectomy in some clinical studies (9)(10)(11), little is known regarding effects of medical management on parathyroidectomy rates in clinical practice. Some reports showed that the laboratory changes observed in clinical practice were less dramatic than those in clinical trials (7), and parathyroidectomy rates decreased through 2004 and 2005 but increased again in 2006 (6).…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of calcitriol, active vitamin D analogs, and cinacalcet has been shown to reduce PTH and although cinacalcet reduced rates of parathyroidectomy in some clinical studies (9)(10)(11), little is known regarding effects of medical management on parathyroidectomy rates in clinical practice. Some reports showed that the laboratory changes observed in clinical practice were less dramatic than those in clinical trials (7), and parathyroidectomy rates decreased through 2004 and 2005 but increased again in 2006 (6).…”
Section: Introductionmentioning
confidence: 99%
“…There were 15 trials comparing cinacalcet to placebo [8, 19-28, 30, 31, 33, 39], 3 trials comparing cinacalcet to standard treatment (i.e., a phosphate binder and/or vitamin D compound) [9, 10, 38], and 6 trials comparing cinacalcet and a vitamin D compound to a vitamin D compound alone [29, 32, 34-37]. Twenty-one trials involved hemodialysis patients [8, 10, 19-24, 26-33, 35-39], 1 trial involved peritoneal dialysis patients [34], and 2 trials enrolled patients on a combination of hemodialysis and peritoneal dialysis [9, 25]. The mean age ranged from 46 to 65 years, and duration of treatment spanned from 7 days to 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-six articles were retrieved for detailed evaluation, of which 24 RCTs with 10,031 participants fulfilled eligibility criteria, and were included in the meta-analysis (Fig. 1) [8-10, 19-39]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations